Evaluasi Web Usability Pada Website ATR/BPN Sumbawa Menggunakan Heuristic Evaluation - Husin Husin; Sabri Balafif; Muhamamad Iqbal (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2022)
Electronic-based government develops in harmony with advances in technology to improve public services. A common problem that often occurs is that many online public service sites do not pay attention to their use so not a few website users get confused, bored, or even lose their way because of an inappropriate appearance. In addition, many online administration sites nev-er evaluate the usability of the website. The focus of this study aims to empirically test the usa-bility of the ATR/BPN Sumbawa website based on the level of severity with the heuristic evalu-ation principle. This research is a quantitative study using a questionnaire with a total of 30 re-spondents, 10 people consisting of active users including ATR/BPN Sumbawa employees, and 20 people who are community users of the website. This research is based on the assessment of ten heuristic evaluation principles with a usability scale system. This research begins with data col-lection, analysis, or testing as well as website assessment and recommendations. The results can be concluded about the evaluation of website usability according to the ten heuristic principles and according to respondents from 43 questionnaire statements as a whole the ATR/BPN Sum-bawa website has fulfilled the 10 heuristic characteristics. Each value in each variable gives an average value agreeing with the indicators in the heuristic principle.